2012
DOI: 10.1371/journal.pone.0041689
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Maternal MTHFR C677T Polymorphism with Susceptibility to Neural Tube Defects in Offsprings: Evidence from 25 Case-Control Studies

Abstract: BackgroundMethylenetetrahydrofolate reductase (MTHFR) is a critical enzyme in folate metabolism and is involved in DNA methylation, DNA synthesis, and DNA repair. In addition, it is a possible risk factor in neural tube defects (NTDs). The association of the C677T polymorphism in the MTHFR gene and NTD susceptibility has been widely demonstrated, but the results remain inconclusive. In this study, we performed a meta-analysis with 2429 cases and 3570 controls to investigate the effect of the MTHFR C677T polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 52 publications
(44 reference statements)
0
54
1
2
Order By: Relevance
“…The most well-studied polymorphism in MTHFR gene is the replacement of the nucleotide thymine by cytosine at position 677 (Ala222Val) (Frosst et al, 1995). This variant, which is relatively common in many populations worldwide, produces a form of methylenetetrahydrofolate reductase that reduces activity at higher temperatures, leading to lower levels of circulating folate (5-methyl-THF), an accumulation of 5, 10-methylene-THF, and increased plasma homocystein levels (Ma et al, 1997;Yan et al, 2012). The frequency of T allele varies in different ethnic population.…”
Section: Evaluation Of the Mthfr C677t Polymorphism As A Risk Factor mentioning
confidence: 99%
“…The most well-studied polymorphism in MTHFR gene is the replacement of the nucleotide thymine by cytosine at position 677 (Ala222Val) (Frosst et al, 1995). This variant, which is relatively common in many populations worldwide, produces a form of methylenetetrahydrofolate reductase that reduces activity at higher temperatures, leading to lower levels of circulating folate (5-methyl-THF), an accumulation of 5, 10-methylene-THF, and increased plasma homocystein levels (Ma et al, 1997;Yan et al, 2012). The frequency of T allele varies in different ethnic population.…”
Section: Evaluation Of the Mthfr C677t Polymorphism As A Risk Factor mentioning
confidence: 99%
“…The prevalence of the MTHFR 677TT genotype varies across ethnic groups and regions, ranging from ,2% in West African and African American populations (8,9) to .35% in some populations such as the northern Chinese and individuals of Mexican descent (8)(9)(10). Meta-analyses reported that mothers or infants with the TT genotype have significantly greater odds of a neural tube defect-affected pregnancy than do those with the CC genotype (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Given the association of the TT genotype with decreased blood folate concentrations (15,16) and increased risk of neural tube defects (11,12,17), understanding the magnitude of the impact that the MTHFR 677C.T polymorphism may have on blood folate concentrations could be critical in assessing the population-level risk of neural tube defects. The objective of this systematic review was to assess the association between MTHFR genotype and blood folate concentrations among women of reproductive age (12-49 y) by applying Bayesian meta-analytic techniques to develop summary estimates of percentage differences between blood folate concentrations by genotype with the use of data from trials and observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…The MTHFR C677T polymorphism is associated with a reduction in the bioavailability of folate and folate metabolites and therefore subjects bearing this polymorphism mimic the stage of very low dietary folate intake (Bagley & Selhub, 1998). Many studies have demonstrated that MTHFR polymorphisms or low levels of folate are directly related to neural tube defects (Yan et al, 2012) and also have now been implicated in the pathogenesis of several diseases and disorders, including leukemia (Pereira et al, 2006;Silva et al, 2013), colorectal cancer (Jokic et al, 2011), cardiovascular disease (Chen et al, 2012), and other congenital abnormalities (Yin et al, 2012).…”
Section: Relationship Between 510-mthfr Polymorphisms Folate Levelsmentioning
confidence: 99%